Enterprise social media use and overload: A curvilinear relationship - Chen, Xiayu; Wei, Shaobo (Journal of information technology, 2019)
Considerable research has focused on the positive effects of information technology use. However, emerging research and practice commentary highlight the importance of considering the negative side of information technology use. The current study investigates how enterprise social media use (i.e. work- and social-related use) influences employees’ perceived overload (i.e. information and social overload), which in turn affects enterprise social media-related strain. In addition, we posit that communication visibility moderates the nonlinear relationship between enterprise social media use and overload. Using a survey of 282 enterprise social media users in the workplace as a basis, we find an inverted U-shaped relationship between work-related enterprise social media use and information overload and between work-related enterprise social media use and social overload. Moreover, a U-shaped relationship is found between social-related enterprise social media use and information overload and between social-related enterprise social media use and social overload. Communication visibility positively moderates the inverted U-shaped relationships between work-related enterprise social media use and information overload and between work-related enterprise social media use and social overload, but negatively moderates the U-shaped relationship between social-related enterprise social media use and information overload. The theoretical and practical implications are also discussed.